The anthropometric criterion in the modelling of evacuation - Dahlke, Grzegorz (Kryterium antropometryczne w modelowaniu warunków ewakuacji, 2020)
The article presents a sample study on the use of anthropometric criteria in modelling evacuation conditions. Formal evacuation models differ in the level of detail they offer in reality mapping. The key parameter determined with their use is evacuation time. The basic data inputs in such modelling are the speed of human movement. Numerous research papers offer examples of such speeds for people of varying ages who wear various clothing (that is more or less restrictive of movements) and footwear. As opposed to movement-based and behavioural models, the models that reflect the basic evacuation parameters fail to account for the number of evacuees. Where human traffic is denser, causing congestion, it is equally essential to consider body dimensions. The article outlines analyses of the impact of changes in anthropometric dimensions in a selected building. Models are rendered using the Pathfinder software. Recommendations are offered on how to assess evacuation conditions for various building types and various occupants
Informatyka Ekonomiczna = Business Informatics, 2020, Nr 1 (55), s. 21-37
Keywords: modelling; evacuation; anthropometry; Pathfinder; human motion simulator; evacuation simulation models; modelowanie; ewakuacja; antropometria; symulator ruchu człowieka; modele symulacyjne ewakuacji